Chimeric specific antigen epitope‐carrying dendritic cells induce interleukin‐17(+) regulatory T cells to suppress food allergy. Issue 2 (2nd December 2019) - Xu, Ling‐Zhi; Xie, Rui‐Di; Xie, Hai; Ju, Ji‐Yu; Fu, Xiao‐Yan; Di, Da‐Lin; Peng, Mei‐Yu; Gao, Wei; Zhang, Yuan‐Yi; Yu, Dian; Liu, Jiang‐Qi; Yang, Gui; et al.
Abstract: Background: The on‐purpose‐modulated dendritic cells (DCs) have shown charming effects on restoring immune regulatory functions in subjects with immune diseases. Objective: This study aims to construct DCs carrying chimerical antigen (Ag) peptides (CAP‐DCs) to induce interleukin (IL)‐17+ inducible Tregs (iTregs) to alleviate food allergy (FA) in a murine model. Methods: In this study, we constructed CAP‐DCs. The CAP is a fusion protein, consisting of a segment of recombinant scFv of anti‐DEC205 antibody and an ovalbumin (OVA) epitope (IC). A murine OVA‐FA model was developed to test the effects of CAP‐DCs on suppressing the allergic response in the intestine. Results: The CAP‐DCs are characterized as that a complex of scFv‐IC is presented on the surface of the cells, moderately express CD80 and CD86 as well as IL‐6, IL‐23, transforming growth factor (TGF)‐β and CCR9. After being passively transferred with CAP‐DCs or injection of scFv‐IC, Ag‐specific IL‐17+ Foxp3+ iTregs were induced in the intestinal lamina propria of FA mice. The iTregs showed immune suppressive effects on Ag‐specific Th2 response. FA mice were adoptively transferred with the CAP‐DCs or scFv‐IC injection, which resulted in a significant decrease in the number of Ag‐specific Th2 cells and suppression of FA response in an Ag‐specific manner. Conclusions and Clinical Relevance: CAP‐DCs can ameliorate FA response by inducing Ag‐specific IL‐17+ Foxp3+ iTregs and suppressing Ag‐specific Th2 response. To generate CAP‐DCs has the translational potential in the treatment of FA.